You are on page 1of 16

 $

 %
0

1  *      

G 
    7               
          *?    
(2 + k 2 )E(x, y, z) = 0

 E(x, y, z)    !      ?       
   !  k = n/c "
    
    
.    / 
 z7      E(x, y, z)  

E(x, y, z) = (x, y, z)eikz

 (x, y, z)     !        


   +

     
      ! z        
 (x, y, z)       E   *?   
E = ()eikz ikzeikz
2 E = (2 )eikz 2ik() zeikz k 2 eikz

   
(2 + k 2 )E = {2 2ik

ikz
}e
=0
z

E                     .9     7


   /      


2


2
z






2k
z

and



2


2
z




2 2




,

x2 y 2

 !              


        
                 
       
        
;'

   

;0

Amplitude varies slowly with z


(on the scale of a wavelength)

wavefront nearly
z
z

  *?        

2 2
+ 2 2ik
=0
2
x
z
z

      

(2T 2ik z
)(x, y, z) = 0



2T = 2 /x2 + 2 /y 2           



  -                     
7

                           


              
     
        
 z           
sin  
-       .     /          7
  >             
         
                  
1

(r ) 2ik
=0
r r r
z

-                   


0 exp{i[P (z) +

kr 2
]}
2q(z)

    B          $7


 9
                 
2ik

dP (z)
k 2 r 2 dq(z)
0
= {2k
+i 2
}0
z
dz
q (z) dz
kr
0
= i
0
r
q(z)

TEM00 %



   

;5

1 0
1
kr 2
(r
) =
{i
0 }
r r r
r r
q(z)
kr 0
2k
0 i
= i
q(z)
q(z) r
2 2
2k
k r
i
}0
= { 2
q (z)
q(z)

        
{



k2r2
dP (z)
2k
k 2 r 2 dq(z)
+
{2k

i
}
+
i
}0 = 0
0
q 2 (z)
q(z)
dz
q 2 (z) dz
k 2 dq(z)
dP (z)
i
2

2k[
[

1]r
+
]r 0 } = 0
2
q (z) dz
dz
q(z)
       r1     
{

     
 r2  r0

 I  

dq(z)
=1
dz
i
dP (z)
=
dz
q(z)

     !      

q(z) = q0 + z

 q0      q  z = 0 $     z = 0      ! 



  % >       q0    -      
      q0       z $
%1  q0     
  q0    
0 exp[i

kr 2
] exp[iP (z)]
2q(r)

kr
  exp[i 2q(r)
] = 1  P (z)       r 1       
   

       r         
                  1       
 
           $r   0% 
   

      q0            !   
M
-  q(z)    q(z) = q0 + z    z    7
      q0 (  
        
D     
         
 ?7      
      q0 = izR  
  4  
2

q(z) = z + izR

 zR          q(z)     .    


 /  
z
zR
1
1
= 2
i 2
=
2
q(z)
z + izR
z + zR
z + zR2

   

;6

   0 
0 exp[

kzR r 2
kzr 2
]
exp[i
] exp[iP (z)]
2(z 2 + zR2 )
2(z 2 + zR2 )

-      P (z)


dP (z)
i
i
=
=
dz
q(z)
z + zR
 z

dz 
0 z  + izR
z
= ln(z  + izR )|0
z
= ln[1 i( )]
zR

iP (z) =

-                  


  
1 i(

z
z
z
) = [1 + ( )2 ]1/2 exp[i tan1 ( )]
zR
zR
zR

exp{iP (z)} = exp{ ln[1 i(

z
)]}
zR

z 1
)]
zR
z
z
= [1 + ( )2 ]1/2 exp[i tan1 ( )]
zR
zR

= [1 i(

               


1
kzR r 2
E(x, y, z)
=
exp[
]
E0
[1 + (z/zR )2 ]1/2
2(z 2 + zR2 )
z
kzr 2
] exp[i tan1 ( )] exp(ikz)
exp[i 2
2
2(z + zR )
zR

  !   .   / $ .    ?/% w0 




w0 =

2zR
k

0 zR
n

"   !                 1 


!       .  ?/ w(z)


w(z) = w0 1 + ( zzR )2

   

;:

          R(z) 


R(z) = z[1 + ( zzR )2 ]

#        
(z) = tan1 ( zzR )

          $TEM00 %     


r2
E(x, y, z)
w0
exp[ 2 ]
=
E0
w(z)
w (z)
2
kr
exp[i
]
2R(z)
exp{i[kz (z)]}

0

/    & 1  *

           $  TEM0,0 %   
           -  

       
    4      
$z = 0%    
           
 
       ! 
R =               
 "    
  
 ?            w(0) = w0    
  w0          ?            
!         R =  q(0) = i nw
      
  

  q(0)   



 
0

zR =

nw02
0

Spot size
w(z)

z
w0
Beam Waist

R(z)
Radius of curvature

   

;;

" 
   
    z 
 
      
   
      w0   G 
 
 zR 
r2
E(x, y, z)
w0
exp[ 2 ]
=
E0
w(z)
w (z)
2
kr
exp[i
]
2R(z)
exp{i[kz (z)}

         ? $    %       


       


  ?

w(z) = w0 1 + (z/zR )2

     

R(z) = z[1 + (zR /z)2 ]

    

(z) = tan1 (z/zR )

        w0  zR         


   
2
zR =

nw0
0

           w0  zR    



    0          n        
w(z) R(z)  (z)       0  n  w0   zR 
 
&   
&  &  & zR

 z = zR 

w(z) = w0 1 + (

zR 2
) = 2w0
zR

  ?  
           2     
1/e     !  zR               
 

  zR     



  $ G 
 
% "  
    b = 2zR     
 4 
     
     

 2
b
2 2w0

2 2w0

2w0

zR

   

;=

-              G 


 

The smaller the waist,
the shorter the Rayleigh range

   

           ?     !  z    


    


w = w0 1 + (
 w0 (

z 2
)
zR

z
) when z
zR
zR

       w  z       !   


 
 

 

w0
w
w0
0
=
=
=
= tan 
2
z
zR
nw0 /0
nw0

w0

    

 
=

0
nw0

  

       w0         





                     z 
 

1
P =
E E dA
2z0
2r 2
1 E02 w02  2 
exp[ 2 ]rdrd
=
2 z0 w 2(z) 0 0
w (z)
2
w0 2
=
E = constant
4z0 0

        
    
      

       
 z7      


   

;A


 

                     



    z = 0    !           
E

1
exp(ikR)
R

 R = (r2 + z2 )1/2 


R
r
z

point
souce

4 z
r 
  R  z         
r 2 1/2
)
z2
1 r2
1 r2
z+
z+
2z
2R

R = z(1 +

*    = kR    !          z7     


 
 
E

kr 2
1
exp(ikz) exp(i
)
R
2R

D 
                   
   R(z)               



 z7  
           
R(z) = z +

zR2
z

    R(z)        ,  


 

at z zR (near waist)
R(z)  2zR at z = zR

z at z
zR (spherical wave)

Z>>ZR

   

=B

                   


      x y               
    !              
  4 z = zR  
      
           G 
 

   
 4 z    zR        
   
     


 & & 

+         


r2
E(x, y, z)
w0
exp[ 2 ]
=
E0
w(z)
w (z)
2
kr
exp[i
]
2R(z)
exp{i[kz (z)]}

 (z) = tan1(z/zR )       7         


  
      7     G 
 
  
        

 2
(Z)
/2

-ZR

ZR

/2

              


      
                       ,
                
          
i

= 2T
z
2k
2
T = 0  

"       
       
"      !     !         
2T = 0
           
   
       2T    
    G 
 
 
       
                     vp = n/c
+                   
    z -         
= kz tan1 (

z
)
zR

   

=&

      
vp =
=

0

wz
wz
=

kz tan1 ( zzR )
c/n
1

0
( 2nz
) tan1 ( zzR )

1  * %   -"./  #




4    


           
 ?        $w(z)  R(z)   %   
 

             q(z)    
                ?     

       q(z)    

q(z) = z + izR

*    q(z)             
 
1
1
z
zR
=
= 2
i 2
2
q(z)
z + izR
z + zR
z + zR2

+ 
   w0 w(z)  R(z)         
     1/q(z) 
1
q(z)

1
R(z)

i0
nw 2 (z)

           q(0)  


    
           R(z)  w(z)   ,  z    

      (      q(z)     
        

            
        

        q(z)      

 "+DJ   
(

   

='

 q(z1 ) = q1      z2 = z1 + d



  

q(z2 ) = q2 = q1 + d

       


        -      
  
q2 =



     

A B
C D

Aq1 + B
Cq1 + D

1 d
0 1

  

* 

 &
& &  
do

di

i
image

object
w1

w2

                         


    R1                  
 
(   o     d0            ?   
     
      w2 = w1 " 
     
      
  R2   
       3
 

      R2                  



 
  i     di 
1
1
1
+ =
d0 di
f

 d0 > 0  di > 0     


           
R1 > 0  R2 < 0   
     (   
   
      
  (  
   o  i 
R1 = d0 , R2 = di

      

  
1
1
1

=
R1 R2
f

   

=0

+ 
        !          

   
  -      7      
   
1
1
i0
=

q1
R1 nw12
1
i0
1
=

q2
R2 nw12

 

1
1
1
1
1

=
R1 R2
q1 q2
f

  
q2 =

1
q1

1
f

q1
Aq1 + B
=
+1
Cq1 + D

qf1

  "+DJ       


 
   
A B
C D

1 0
f1 1

    (  "+DJ      


  
   M
                    
    2
                


q2 =



A B
C D

Aq1 + B
Cq1 + D

      
    

          "+DJ   2 #      

  
         "+DJ            
                     
                    
H 2 
   
zR

f
2w0'

w0

   


     2

=5

i0
1
1

=
q1
nw02

q1 = i

 
    


A B
C D

1 d
0 1

nw02
0



1 0
f1 1

1 fd d
f1 1

" 
nw 2

q2 =

1
R2

(1 fd )(i 0 0 ) + d
1
i0 =
nw 2
nw
2
f1 (i 0 0 ) + 1
2

  zR = nw
          

2
0

1 i zfR
1
i0

=
R2 nw22
izR (1 fd ) + d
=

2
zR
(1
f

fd ) i[ fd zR + (1 fd )zR ]
d2 + (1 fd )2 zR2

2
zR
(1
f

fd ) izR

d2 + (1 fd )2 zR2

+  
    
       
        
  
d
1
d

f (1 f )
1
z2
= dR 2
R2
( zR ) + (1 fd )2

R2 (d) =

#  
  


( zdR )2 + (1 fd )2
d
2
zR

f1 (1 fd )

zR
0
= 2
2
nw2
d + (1 fd )2 zR2
nw22
d2
d
= 2 zR + (1 )2 zR
0
zR
f

       ?     


w22 (d) = w02(1

d 2
d
) + w02 ( )2
f
zR

   

=6

           R2(d) = 1     


 R2 (d)     ?
1
d
d
(1 ) = 0
2
zR f
f
1
1
1
d( 2 + 2 ) =
zR f
f
1/f
d=
2
1/zR + 1/f 2
f
d=
1 + f 2 /zR2

-    zR
f  
 d = f  $            

  ? w0
f 0/n          
% - 
         w0  


 d     ?    


f
)]2
2
2
1 + f /zR
f
f
= w02 {[1
]2 }
]2 + [
f2
f2
(1 + z 2 )f
(1 + z 2 )zR

(w0 )2 [w2 (d =

2
2
( f2 )2 + zf2
2 zR
R
w0
2
(1 + zf2 )2
R

= (

0 f 2 1
)
2
nw0 1 + zf2

           




w0 =

"
     zR
f

1
0 f

nw0 1 +

f2
2
zR

0 f
nw0
  & '


w0 

-   !     

D0 = 2w0 , D0 = 2w0

           




D0 =

4
f
40 f
= ( )
n(2w0 )
D0

         


  = 0/n J!
    
               
f =

f
D0

   

=:

-       f  !              


  4  1.27


D0 = 1.27f 

                


         
   D0 


0

2%&# 1  *

                       

              "


        7
          . /  .  /    
"  
7                  
 C                   
 . /  . /                 
                          
  D                    

   


2x
2y
E(x, y, z) = Em,p Hm
Hp

w(z)
w(z)


w0
x2 + y 2

exp 2
w(z)
w (z)


exp j kz (1 + m + p) tan1

kr 2
exp j
2R(z)

z
zR



 m  p      
    . /    1
Em,p    
 1     w(z) w0  zR  R(z)   ! 
      
7         
 T EMm,p             (    T EM0,0
    Hm(u)     (
 
  m
m u2 d

Hm (u) = (1) e

m u2

e
dum

-                     


                7        
                        
          m  p   ( 
       
   *                7
 2
H0 (u) = 1

   

=;

H1 (u) = 2u
H2 (u) = 2(2u2 1)

  !                  


 !
  $          !%

-     
 x $ y %               
 . /  
     z   +    x  !   !
         
  ?  !     
        !
  ?        
m              m + 1 ./   


    x                  y    
*      (m + 1)(p + 1) ./ T EMm,p  C        
     w(z)          
   
           
  
7